he Effect Of Cooperative Learning Style And Exercises Scheduling On The Development Of Some Basic Skills In Volleyball For Forth Year Preparatory School Students - Abbas, Ahmed; Alwan, Bahera (Journal of Physical Education, 2017)
he research consisted five chapters. In the first chapter included the introduction, importance, problem and aims of the research. The second chapter included the theoretical and similar studies concentrating on cooperative learning. The third chapter included the procedures, the method used in the research, the subjects, the pilot study, pretests, main experiment and posttests. The data was collected and treated using proper statistical operation. The results showed that cooperative learning using scheduled training have a positive effect on developing basic skills in volleyball